Are subjective distributions in inflation expectations symmetric? - Nikola Mirkov; Andreas Steinhauer (University of Zurich, Department of Economics, 2014)
We conducted an anonymous survey in December 2013 asking around 200 economists worldwide to provide an interval (a to b) of average inflation in the US expected "over the next two years". The respondents were also instructed to give a probability of inflation being higher or lower than the mid-interval (a+b)/2. The aggregate distribution of inflation expectations we obtain closely resembles the outcome of the Survey of Professional Forecasters for 1Q2014. More importantly, we find that the subjective probability mass on either side of the mid-interval is not statistically different from 0.5, which means that the subjective distributions are symmetric. Our results align well with several papers evaluating the Survey of Professional Forecasters or similar data sets and finding no significant departures from symmetry.
Keywords: C42; E31; 330; inflation expectations; subjective probability distributions